World Water Assessment Programme Sri Lanka case study, Ruhuna basins: proceedings of a Workshop held at Koggala Beach Hotel, Sri Lanka, 7-9 April 2002 - Imbulana, K.A.U.S.; Droogers, Peter; Makin, Ian W. (International Water Management Institute, 2002)
The Case Study Workshop was organized with the objective of obtaining the necessary input the experts on different subject areas of water resources, subject those views and discussion among the stakeholder agencies, and synthesize the information to a report on the case study. The outcome of the Workshop would eventually transform into the contribution of Sri Lanka to the forst WWDR.